PDK1 is a potential therapeutic target against angiosarcoma cells. Issue 1 (April 2015) - Wada, Makoto; Horinaka, Mano; Yasuda, Shusuke; Masuzawa, Mikio; Sakai, Toshiyuki; Katoh, Norito
Highlights: The PI3K inhibitor and mTOR inhibitor induced G1 cell cycle arrest. Cyclin D levels were decreased by knockdown of PDK1, not by AKT inhibitor. The knockdown of PDK1 inhibited colony formation than the mTOR inhibitor. Abstract: Background: Angiosarcoma is a rare and aggressive malignant neoplasm of endothelial cells. Recent studies have shown that the mTOR pathway is also aberrantly activated in cutaneous angiosarcoma. New therapeutic strategies are required because the prognosis of this disease is still poor. Objective: The aim of the present study was to determine the driver gene of angiosarcoma useful for the screening of small molecule inhibitors. Methods: We investigated the sensitivity of inhibitors for the PI3K/AKT/mTOR pathway in ISOS-1 and ISO-HAS cutaneous angiosarcoma cell lines. Flow cytometric analysis was conducted to evaluate cell-cycle progression and apoptosis. Western blot analyses were performed to elucidate the possible underlying mechanisms of growth inhibition. The colony formation assay was conducted to evaluate the clonogenic potential. We used the siRNA for PDK1 to examine the role of PDK1 on the growth of angiosarcoma cells. Results: The PI3K inhibitor and mTOR inhibitor inhibited the growth of both cell lines in a dose-dependent manner. The PI3K inhibitor more effectively induced cell-cycle arrest at the G1 phase with the downregulated expression of cyclin D in ISOS-1 cells than the mTOR inhibitor. The PI3K inhibitor and mTOR inhibitor weakly but significantly induced G1 cell cycle arrest at the same degree in ISO-HAS cells. The expression of cyclin D was downregulated by the treatment with siRNA for PDK1, but not by the AKT inhibitor in ISOS-1 and ISO-HAS cells. The knock down of PDK1 with siRNA was more effective at reducing colony numbers than the mTOR inhibitor in ISOS-1 cells. Conclusion: These data showed that PDK1 played a pivotal role in the growth of angiosarcoma cells. Therefore, inhibition of PDK1, but not AKT, may be a more appropriate strategy than that of mTORC1 for the treatment of cutaneous angiosarcoma; the PDK1 inhibitor is promising as a therapeutic agent.